Failure mode analysis of a 1.9 turbo diesel engine crankshaft. (July 2019) - Mateus, J.; Anes, V.; Galvão, I.; Reis, L.
Abstract: This paper reports a failure mode analysis of a 1900 cm 3 turbo diesel engine of a well-known commercial brand. The engine is a supercharged diesel engine with turbocharger, producing a maximum power of 81 kW; it was produced in 1999 and collapsed at 120, 000 km without warning. A fracture occurred at the crankpin n°1 of the crankshaft in the region of web-fillet. Crankshafts are mechanical power transmission components with complex geometries and experience multiaxial stress states in main journals and crankpins. The objective of this work is to determine the root cause that led to the crankshaft collapse. A fractographic, metallographic, and numeric analysis were performed to understand the crankshaft failure mode and its mechanical mechanisms. Results show that the crankshaft failure resulted from a fatigue process governed by normal stresses raised by two possible processes, namely, a notch in the crack initiation spot, or the crankshaft misalignment. Highlights: A failure mode of a 1900 cm 3 turbo diesel crankshaft was studied. A fractographic and metallographic analysis was performed. A finite element model was implemented to study stress levels on the crack initiation spot. Multiaxial critical plane models were used to estimate the crack initiation plane. The crankshaft failure resulted from a fatigue process in crankpin n°1.